Modern electric, hybrid electric, and fuel cell vehicles - Ehsani, Mehrdad; Gao, Yimin; Longo, Stefano; Ebrahimi, Kambiz (Boca Raton, FL : Taylor & Francis, CRC Press, 2018)
his text delivers expanded and detailed coverage of the fundamentals, theory and design of electric, hybrid electric, and fuel cell vehicles.
Previous edition: 2010.
Includes bibliographical references and index.
EEE
Parama Publishers
Keywords: Hybrid electric vehicles; Fuel cells; Electrical engineering